III.iv.3. The Ionian Islands under British protection. - Kennedy, John Pitt, 1796-1879 (London: James Ridgway, 1851)
Contains the signature of John Pitt Kennedy, signed "JP Kennedy Lt. Col."
Authorship attributed to Sir George Ferguson Bowen (1821-1899).
Keywords: Great Britain -- Colonies -- Administration; Ionian Islands (Greece)